I See You Sisters Like Yesterday Today: The Unnatural and Accidental Women - Sullivan, Sharon (Atlantis, 2013)
This paper argues that Marie Clements’ play, The Unnatural and Accidental Women, promotes a (re)creation of a women’s community that empowers women and nurtures individual identity. Inspired by the true story of women murdered by a serial killer in Vancouver, British Columbia, Clements focuses on the indigenous women victims whose stories were not told in the media.